Economic analysis of waste power plants based on the economic scale -Case study Merah Putih waste power plant - Amrico, Hendrik; Dalimi, Rinaldy (Universitas Negeri Padang, 2023)
Jakarta's dense population creates problems with the high daily waste production, which reaches 7,500 tons. On the other hand, the open dumping method in the final waste treatment creates another problem in the form of greenhouse gas emissions. The regional government also issued a policy to reduce greenhouse gas emissions to achieve net zero emission by 2050. The solution that then emerged for the two problems above was to convert waste into electrical energy through incineration technology. This study aims to conduct an economic analysis in the context of implementing incineration technology. The results showed that the minimum capacity for economic feasibility was 8 MW with an LCoE of IDR 2,578.32/kWh, 429 tonnes of waste per day, an IRR of 8.63%, and an NPV of IDR 115,038,835,638.12 at an investment value of IDR 505.877.074.317